2013
DOI: 10.18061/1811/53699
|View full text |Cite
|
Sign up to set email alerts
|

Racial/Ethnic Variations in Violence Against Women: Urban, Suburban, and Rural Differences

Abstract: A large literature shows that violence against women in intimate relationships varies across racial/ethnic groups. However, it is unclear whether such variations differ across urban, suburban, and rural areas. The main objective of this article is to examine this issue using 1992 to 2009 National Crime Victimization Survey data. We also test the hypothesis that racial/ethnic minority women living in rural areas are more likely to be assaulted by their current and former intimate partners than are their urban a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 32 publications
(28 reference statements)
0
13
0
1
Order By: Relevance
“…Recall that existing literature presents perplexing inconsistencies including that estimates of IPV incidence are not always highest in urban settlements. In fact, the research on the effects of settlement type on IPV using the BJSUSR variable is largely equivocal as to whether the incidence of IPV against women living in rural settlements is higher, lower, or similar to that in other areas (Bachman ; Bachman and Saltzman ; DeKeseredy et al ; Greenfeld et al 1998; Rennison et al ; Rennison and Welchans ; Truman and Morgan ; Wolf Harlow ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recall that existing literature presents perplexing inconsistencies including that estimates of IPV incidence are not always highest in urban settlements. In fact, the research on the effects of settlement type on IPV using the BJSUSR variable is largely equivocal as to whether the incidence of IPV against women living in rural settlements is higher, lower, or similar to that in other areas (Bachman ; Bachman and Saltzman ; DeKeseredy et al ; Greenfeld et al 1998; Rennison et al ; Rennison and Welchans ; Truman and Morgan ; Wolf Harlow ).…”
Section: Discussionmentioning
confidence: 99%
“…Of the eight studies that have used NCVS/NCS to compare the incidence of IPV against women residing in urban and rural settlements, only three have found that the incidence of IPV was higher in the former (Greenfeld et al 1998;Truman and Morgan 2014). Otherwise, although estimated urban rates were nominally greater than the rural rates, apparent differences were not statistically significant (Bachman 1994;Bachman and Saltzman 1995;DeKeseredy, Dragiewicz, and Rennison 2012;Rennison and Welchans 2000;Wolf Harlow 1991).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Carrington et al 2013;Hall-Sanchez 2014;Hogg and Carrington 2006;Sherman 2005), urban, suburban and rural differences in violence against women (e.g. DeKeseredy et al 2012;Rennison et al 2012aRennison et al , 2013aRennison et al , 2013b, and place-based analyses (e.g. Hall-Sanchez 2014; Pruitt 2008).…”
Section: Violence Against Rural Women: Developing Researchmentioning
confidence: 99%
“…The statistic is astounding, yet despite its widespread occurrence much of the research on IPV continues to focus on urban settings, overlooking the unique experiences of abused rural women. Current research suggests that IPV rates are similar in urban and rural areas (DeKeseredy, Dragiewicz and Rennison, 2012); however, despite the equivalent nature of its occurrence, rural IPV has seen a profound lack of attention and documentation. There are two sets of findings that prompt a focus on rural areas.…”
Section: Introductionmentioning
confidence: 99%